STUDI ANATOMI OTAK MUSANG LUWAK (Paradoxurus hermaphroditus) ASAL PULAU TIMOR - Andry Ndula Rimu; Yulfia N Selan; Filphin A. Amalo (Jurnal Veteriner Nusantara, 2020)
Asian Palm Civet (Paradoxurus hermaphroditus) is one of Indonesian faunas. The brain is the most vital organ for living organism because it is a central coordination of the various activities, internal mechanisms and coordinating all body activities related to the stimulation of the surrounding environment. The purpose of this research was to observe the brain macroscopic representation of Asian palm civet. Three Asian palm civets were used in this study. Asian Palm Civet was anaesthetized and perfused then opened the skull to observe the brain macroscopic representation. The brain macroscopic representation showed that the Asian palm civet had 3 parts of brain the cerebrum, cerebellum and brain stem. Sulcus and gyrus in Asian palm civet are simpler than dogs. Paraflocculus lobes in the dog is more complicated compare to Asian palm civet that is found on the ventral and dorsal. Vermisin the Asian Palm civet resemblance to the vermis in dog. The continued development of the vermisin Asian palm civet and more developed than the fruit bat (Rousettus sp), in connection with the Asian palm civet life as nocturnal and live in tree.